A Simple Cleaning Intervention to Prevent Transmission of Carbapenemase-Producing Enterobacterales from Hospital Sinks. (October 2020) - Kwong, Jason; Leroi, Marcel; Bannam, Trudi; Edmonds, Deidre; Grabsch, Elizabeth; Narayanasamy, Shanti; Greenough, John; Lane, Courtney; Easton, Marion; Howden, Benjamin; Johnson, Paul; Grayson, M.
Abstract : Background: A prolonged outbreak of carbapenemase-producing Serratia marcescens (CPSM) was identified in our quaternary healthcare center over a 2-year period from 2015 through 2017. A reservoir of IMP-4–producing S. marcescens in sink drains of clinical hand basins (CHB) was implicated in propagating transmission, supported by evidence from whole-genome sequencing (WGS). We assessed the impact of manual bioburden reduction intervention on further transmission of CPSM. Methods: Environmental sampling of frequently touched wet and dry areas around CPSM clinical cases was undertaken to identify potential reservoirs and transmission pathways. After identifying CHB as a source of CPSM, a widespread annual CHB cleaning intervention involving manual scrubbing of sink drains and the proximal pipes was implemented. Pre- and postintervention point prevalence surveys (PPS) of CHB drains performed to assess for CPSM colonization. Surveillance for subsequent transmission was conducted through weekly screening of patients and annual screening of CHB in transmission areas, and 6-monthly whole-hospital PPS of patients. All CPSM isolates were assessed by WGS. Results: In total, 6 patients were newly identified with CPSM from 2015 to 2017 (4.3 transmission events per 100, 000 surveillance bed days [SBD]; 95% CI, 1.6–9.4). All clinical CPSM isolates were linked to CHB isolates by WGS. The CHB cleaning intervention resulted in a reduction in CHB colonization with CPSM in transmission areas from 72% colonization to 28% (ARR, 0.44; 95% CI, 0.25–0.63). A single further clinical case of CPSM linked to the CHB isolates was detected over 2 years of surveillance from 2017 to 2019 following the implementation of the annual CHB cleaning program (0.7 transmissions per 100, 000 SBD; 95% CI, 0.0–3.9). No transmissions were linked to undertaking the cleaning intervention. Conclusions: A simple intervention targeted at reducing the biological burden of CPSM in CHB drains at regular intervals was effective in preventing transmission of carbapenemase-producing Enterobacterales from the hospital environment to patients over a prolonged period of intensive surveillance. These findings highlight the importance of detailed cleaning for controlling the spread of multidrug-resistant organisms from healthcare environments. Funding: None Disclosures: Jason Kwong, Austin Health